KINERJA PENYULUH PERTANIAN LAPANGAN (PPL) TERHADAP PRODUKSI USAHA TANI PADI DI DESA AIR LATAK KECAMATAN SELUMA BARAT KABUPATEN SELUMA - Dika Juniarti; Evi Andriani; Ana Nurmalia (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2021)
The performance of field agricultural extension should be directly related to the production of lowland rice farmers. This study aims to determine the performance and role of agricultural extension on the production of rice farming in Air Latak Village, Seluma Barat District, Seluma Regency. The research method used was to determine the performance of field agricultural extension with qualitative descriptive methods. Samples were taken, namely all field agricultural extension agents at the Talang Dantuk Agricultural Extension Center, Seluma Regency. To analyze the relationship between the role of agricultural extension agents using qualitative and quantitative methods. The sampling method used was random, with 30 respondents. The performance of field agricultural extension at the Talang Dantuk Agricultural Extension Center in Seluma Regency was categorized as good with an average of 79.58 and in the research area it was categorized as good with a work value of 78.75. The role of Field Agricultural Extension (PPL) has a strong relationship to rice farming production. the role of Field Agricultural Extension (PPL) as a desiminator, facilitator, consultator has a real or significant relationship to lowland rice production. the role of Field Agricultural Extension (PPL) as a desiminator, facilitator, consultator has a real or significant relationship to lowland rice production.